1995
DOI: 10.1039/c39950001507
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption and EPR studies on a six-coordinate iron(III)–tetramesitylporphyrin–hydrogen peroxide complex having a nitrogenous axial ligand

Abstract: The formation of a six-coordinate FeiiiTMP-hydrogen peroxide complex (TMP = tetramesitylporphyrin), having a nitrogenous ligand at the axial position, is demonstrated by means of simultaneous EPR and optical absorption measurements a t 77 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 12 publications
7
34
0
Order By: Relevance
“…(9); (---) kinetic rate for 5-hydroxycamphor formation, k ) 0.0035 s -1 ; (---) kinetic rate for autooxidation of putidaredoxin, k ) 0.007 s -1 (Sligar et al, 1974); (s) kinetic rate for 1.0 equiv of oxidized putidaredoxin formed in 1 s and 1.1 equiv autooxidize at the same rate above, k ) 0.007 s -1 . Coon, 1981;Davydov et al, 1991;Kappl et al, 1985;Nyman & Debrunner, 1991;Tajima et al, 1993) and observed model compounds (Balch, 1992;Tajima et al, 1995;Yamaguchi et al, 1993). The spectral intermediate observed with D251N is distinct from these species in both its UV-visible spectra and EPR spectra (Balch, 1992;Blake & Coon, 1981;Davydov et al, 1991;Kappl et al, 1985;Nyman & Debrunner, 1991;Tajima et al, 1993Tajima et al, , 1995Yamaguchi et al, 1993), suggesting the rate-determining step is the first proton transfer (5A and B to 5C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(9); (---) kinetic rate for 5-hydroxycamphor formation, k ) 0.0035 s -1 ; (---) kinetic rate for autooxidation of putidaredoxin, k ) 0.007 s -1 (Sligar et al, 1974); (s) kinetic rate for 1.0 equiv of oxidized putidaredoxin formed in 1 s and 1.1 equiv autooxidize at the same rate above, k ) 0.007 s -1 . Coon, 1981;Davydov et al, 1991;Kappl et al, 1985;Nyman & Debrunner, 1991;Tajima et al, 1993) and observed model compounds (Balch, 1992;Tajima et al, 1995;Yamaguchi et al, 1993). The spectral intermediate observed with D251N is distinct from these species in both its UV-visible spectra and EPR spectra (Balch, 1992;Blake & Coon, 1981;Davydov et al, 1991;Kappl et al, 1985;Nyman & Debrunner, 1991;Tajima et al, 1993Tajima et al, , 1995Yamaguchi et al, 1993), suggesting the rate-determining step is the first proton transfer (5A and B to 5C).…”
Section: Resultsmentioning
confidence: 99%
“…This argues that the new intermediate precedes O-O bond heterolysis (5C to 6) since O-O bond heterolysis must also occur in peroxide-supported catalysis (Tajima et al, 1993;Egawa et al, 1994;Ortiz de Montellano, 1995b). In the hydrogen peroxide and alkylhydroperoxide supported catalysis, a ferric hydroperoxo (5C) or similar ferric alkylperoxo intermediates are proposed to be formed under nonphysiological conditions (Balch, 1992;Blake & Coon, 1981;Tajima et al, 1993Tajima et al, , 1995Yamaguchi et al, 1993). EPR and UV-visible signals for ferric hydroperoxo intermediates are well established from a variety of nonphysiological protein-based intermediates (Blake & 2 If the rate-determining step was the second electron transfer (4 to 5A-B), the kinetics of oxidized Pd formation would be expected to be a mixture of the rate of 5-hydroxycamphor formation (---in Figure 5) and autooxidation of excess reduced Pd (---in Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…9 It also exhibited an EPR spectrum (77 K) indicative of a low-spin ferric complex with anomalously small g anisotropy. The peroxide complexes Fe 3+ -OEP(OOH) 212 and Fe 3+ "TMP(OOH) 213 were also reported. The EPR spectra of these peroxide complexes contrasted with those of the high-spin ferric peroxo porphyrin complexes discussed earlier and were consistent with those of Fe m (hemoglobin)(OOH) and Fe'"(horseradish peroxidase)(OOH).…”
Section: Heme and Pseudo-heme Iron Dioxygen Complexesmentioning
confidence: 92%
“…Axial ligand exchange was also demonstrated in the case of complex 20 ( Figure 8), which was prepared by the addition of imidazole to a solution of the hydroxide precursor [59].…”
Section: Fe(iii)-hydroperoxo (Alkylperoxo) Intermediatesmentioning
confidence: 97%